Active Surveillance Beyond 5 Years Is Required for Presumed Branch‐Duct Intraductal Papillary Mucinous Neoplasms Undergoing Non‐Operative Management. (July 2017) - Crippa, Stefano; Pezzilli, Raffaele; Bissolati, Massimiliano; Capurso, Gabriele; Romano, Luigi; Brunori, Maria Paola; Calculli, Lucia; Tamburrino, Domenico; Piccioli, Alessandra; Ruffo, Giacomo; Fave, Gianfranco Delle; Falconi, Massimo
Abstract : Objectives: To evaluate the results of active surveillance beyond 5 years in patients with branch‐duct intraductal papillary mucinous neoplasms (BD‐IPMNs) without worrisome features (WF) and high‐risk stigmata (HRS) undergoing non‐operative management. Methods: Patients with a minimum follow‐up of 5 years who underwent surveillance with at least yearly magnetic resonance imaging were included. New onset of and predictors of WF/HRS during follow‐up as well as long‐term survival were analyzed. Results: In all, 144 patients were followed for a median of 84 months. At diagnosis multifocal BD‐IPMNs were found in 53% of cases and mean size of the largest cyst was 15.5 mm. Changes during follow‐up were observed in 69 patients (48%). New onset of WF/HRS were observed in 26 patients (18%) but the rate of HRS was only 4%. WF and HRS developed after a median follow‐up of 71 and 77.5 months from diagnosis, respectively, and without previous changes in 19/26 patients. Independent predictors of WF/HRS development were size at diagnosis>15 mm, increase in number of lesions, main pancreatic duct growth rate ≥0.2 mm/year, cyst growth rate >1 mm/year. Overall, the rate of pancreatic invasive malignancy was 2% and the 12‐year disease‐specific survival was 98.6%. Conclusions: Long‐term nonoperative management is safe for BD‐IPMNs without WF and HRS. Discontinuation of surveillance cannot be recommended since one out of six patients developed WF/HRS far beyond 5 years of surveillance and without previous relevant modifications. An intensification of follow‐up should be considered after 5 years.